The cross-section of firms over the business cycle : new facts and a DSGE exploration - Ruediger Bachmann; Christian Bayer (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using a German firm-level data set, this paper is the first to jointly study the cyclical properties of the cross-sections of firm-level real value added and Solow residual innovations, as well as capital and employment adjustment. We find two new business cycle facts: 1) The cross-sectional standard deviation of firm-level innovations in the Solow residual, value added and employment is robustly and significantly countercyclical. 2) The cross-sectional standard deviation of firm-level investment is procyclical. We show that a heterogeneous-firm RBC model with quantitatively realistic countercyclically disperse innovations in the firm-level Solow residual and non-convex adjustment costs calibrated to the non-Gaussian features of the steady state investment rate distribution, produces investment dispersion that positively comoves with the cycle, with a correlation coefficient of 0.58, compared to 0.45 in the data. We argue more generally that the cross-sectional business cycle dynamics impose tight empirical restrictions on structural parameters and stochastic properties of driving forces in heterogeneous-firm models, and are therefore paramount in the calibration of these models.
Keywords: E20; E22; E30; E32; 330; Ss model; RBC model; cross-sectional firm dynamics; lumpy investment; countercyclical risk; aggregate shocks; idiosyncratic shocks; heterogeneous firms; Real Business Cycle; Produktivität; Schock; Konjunktur; Risiko; Innovation; Investition; Dynamisches Gleichgewicht; Theorie; Deutschland